2019
DOI: 10.1002/pits.22309
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to peer influence during middle school: Links with social support, peer harassment, and gender

Abstract: The present study explores concurrent relations between social support, gender, susceptibility to peer influence, and peer‐based aggression and harassment in a socioeconomically and racially diverse sample of 774 seventh and eighth grade students. Results indicate that students perceiving lower support from their family or school were relatively more likely to be highly susceptible to peer influence, and to have friends who they believed were also highly susceptible to peer influence. Further, higher susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 130 publications
1
6
0
Order By: Relevance
“…Whereas prior work has focused on other forms of sexual violence and on male perpetrators, our findings demonstrate the predictive utility of the peer environment on sexual harassment, and for females in particular. These findings complement emerging evidence finding that girls are especially susceptible to negative peer influence, which in turn may lead to increased involvement in peer-based harassment (Goldstein et al, 2020). Future work should explore additional contextual factors, such as the school environment, to help elucidate how peers may influence harassing behaviors, among girls in particular.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Whereas prior work has focused on other forms of sexual violence and on male perpetrators, our findings demonstrate the predictive utility of the peer environment on sexual harassment, and for females in particular. These findings complement emerging evidence finding that girls are especially susceptible to negative peer influence, which in turn may lead to increased involvement in peer-based harassment (Goldstein et al, 2020). Future work should explore additional contextual factors, such as the school environment, to help elucidate how peers may influence harassing behaviors, among girls in particular.…”
Section: Discussionsupporting
confidence: 85%
“…That said, these studies have mainly focused on male perpetrators, with scarce attention to female sexual harassment perpetration. However, a recent study examining peer influence on adolescents’ peer-based harassment (relational aggression and sexual harassment), found that girls who were highly vulnerable to peer influence had a greater risk for being both a victim and perpetrator of relational aggression as well as a victim of sexual harassment, compared to boys (Goldstein et al, 2020). Although peer influence did not predict sexual harassment perpetration for girls, findings nevertheless indicate that peer influence may be a unique risk factor worthy of further exploration.…”
Section: Relational Factors Associated With Sexual Violence Perpetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…One study seemed in line with the desensitization hypothesis, as persistent victimization did not relate to peer perception (Ladd & Troop-Gordon, 2003). A finding that did not fit any of the hypotheses was that victimization, especially for girls, related to thinking one's friends are susceptible to peer influence (Goldstein et al, 2020). Speculatively, this perception might relate to negative peer experiences where friends do not stand up for victimized youth and join in on negative behaviors of others in the peer group.…”
Section: Peer Perceptionmentioning
confidence: 98%
“…Parental neglect could weaken adolescents' attachment to their parents and increase their risk of engaging in delinquent behaviors (Trickett et al, 2011). A previous study showed that when adolescents were neglected by their parents, they were easily influenced by deviant peers, which could increase the chances of relational and sexual victimization (Goldstein et al, 2020). Additionally, children who were neglected by their parents tended to perceive lower parental support or failed to deal with the negative psychological problems caused by bullying in a timely manner (Herráiz & Gutiérrez, 2016).…”
Section: Family Level Correlates and Bullying Victimizationmentioning
confidence: 99%